Individual characteristics of students with autism spectrum disorders and school refusal behavior. (February 2019) - Munkhaugen, Ellen Kathrine; Torske, Tonje; Gjevik, Elen; Nærland, Terje; Pripp, Are Hugo; Diseth, Trond H
This study compared social, executive, emotional, and behavioral characteristics of students with autism spectrum disorder who did and did not display school refusal behavior. The participants were 62 students with autism spectrum disorder without intellectual disability aged 9–16 years attending inclusive schools. Parents first completed questionnaires assessing social and executive functioning as well as emotional and behavioral problems. They then documented their child's school refusal behavior for a period of 20 days. Compared to students without school refusal behavior (n = 29), students with school refusal behavior (n = 33) were significantly less socially motivated; displayed more deficits in initiating tasks or activities, in generating ideas, responses, or problem-solving strategies; and displayed more withdrawn and depressive symptoms. Assessing social and executive functioning, as well as emotional problems, may help professionals provide tailored interventions for students with autism spectrum disorder and school refusal behavior, which will further be valuable in recognizing characteristics associated with school refusal behavior.